2017
DOI: 10.1364/boe.8.005179
|View full text |Cite
|
Sign up to set email alerts
|

Multimode fibre based imaging for optically cleared samples

Abstract: Optical clearing is emerging as a popular approach particularly for studies in neuroscience. However the use of corrosive clearing solutions typically requires sophisticated objectives or extreme care with optical components chosen for single- or multi-photon imaging. In contrast to the use of complex, custom-made microscope objectives, we show that the use of a corrected multimode fibre (MMF) offers a route that is resistant to corrosion, can be used in clearing media, is not constrained by the refractive ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A sapphire fiber Raman imaging probe of diameter 60 micrometer, which can be used for endoscopic applications (in this case, a cladding will be required) and potentially for high temperature detections, is presented in this paper. This probe performs imaging without any mechanical motion and without any focusing optics at the tip, which makes it particularly interesting in harsh environments such as high temperature and/or in contact with corrosive liquids [29] and gases.…”
Section: Discussionmentioning
confidence: 99%
“…A sapphire fiber Raman imaging probe of diameter 60 micrometer, which can be used for endoscopic applications (in this case, a cladding will be required) and potentially for high temperature detections, is presented in this paper. This probe performs imaging without any mechanical motion and without any focusing optics at the tip, which makes it particularly interesting in harsh environments such as high temperature and/or in contact with corrosive liquids [29] and gases.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Gusachenko et al first employed MFSE for Raman spectroscopic imaging by replacing the photodetector in the common reflection imaging modality with the spectral measurement module as shown in Fig. 9(a) 142 . A continuous laser with 532 nm wavelength was focused by the MMF as the excitation beam to induce Raman scattering on the sample pixel-by-pixel.…”
Section: Raman Imagingmentioning
confidence: 99%
“…NA: numerical aperture of MMF; P: detector; S: light source; SK: CARS Stokes beam; PMT: Photomultiplier tube; FOUS: fiber-optic ultrasound sensor; R l and R a are the lateral and axial resolution, respectively; O: optical sectioning; A: acoustic sectioning; FWM: fourwave mixing.analysis of chemical compounds or biological substances by employing Raman imaging modalities, CARS imaging modalities, and second harmonic generation imaging modalities. For example, Gusachenko et al demonstrated using Raman imaging modalities of MFSE to identify the spatial distribution of different pharmaceuticals in samples142 . Cifuentes et al successfully employed the polarization-resolved second harmonic generation imaging modality of MFSE to characterize different structural proteins in the mouse tail tendon and heart tissue148 .…”
mentioning
confidence: 99%
“…This subject arises other interests and a myriad of applications among them micromanipulation [20], optical clearing [21] and optical tweezers [22]. Also multimode imaging brings direct applicabilities to the biological field, like endoscopes composed of a single MMF or either a bundle of them which offers more independent channels to the the imaging system [23,24].…”
Section: Wavefront Shapingmentioning
confidence: 99%